2018
DOI: 10.1186/s12936-018-2294-5
|View full text |Cite
|
Sign up to set email alerts
|

A systematic and prospectively validated approach for identifying synergistic drug combinations against malaria

Abstract: BackgroundNearly half of the world’s population (3.2 billion people) were at risk of malaria in 2015, and resistance to current therapies is a major concern. While the standard of care includes drug combinations, there is a pressing need to identify new combinations that can bypass current resistance mechanisms. In the work presented here, a combined transcriptional drug repositioning/discovery and machine learning approach is proposed.MethodsThe integrated approach utilizes gene expression data from patient-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 53 publications
(61 reference statements)
1
24
0
Order By: Relevance
“…The library of 23 compounds that were selected for prospective validation resulted from predictions generated by a developmental version of CoSynE that had previously virtually screened 21 million DrugBank combinations using the same training data, alongside a different approach that was developed in parallel to CoSynE (KalantarMotamedi et al, 2018 ; see Experimental section for details). From this library of 23 compounds (and a possible 253 combinations), a total of 20 combinations comprising 12 distinct individual compounds were predicted to be synergistic, and these were submitted for prospective experimental validation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The library of 23 compounds that were selected for prospective validation resulted from predictions generated by a developmental version of CoSynE that had previously virtually screened 21 million DrugBank combinations using the same training data, alongside a different approach that was developed in parallel to CoSynE (KalantarMotamedi et al, 2018 ; see Experimental section for details). From this library of 23 compounds (and a possible 253 combinations), a total of 20 combinations comprising 12 distinct individual compounds were predicted to be synergistic, and these were submitted for prospective experimental validation.…”
Section: Resultsmentioning
confidence: 99%
“…The approach by KalantarMotamedi et al ( 2018 ) differs from that described in this work primarily by the usage of gene expression data. Firstly, differential gene expression profiles of mild vs. severe malaria patient peripheral blood samples were used to predict potentially active single antimalarial agents by comparison of drug gene perturbations through a modified Gene Set Enrichment Analysis (GSEA) approach (Subramanian et al, 2005 ) applied to the Library of INtegrated Cellular Signatures (LINCS) Phase I database (Subramanian et al, 2017 ).…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…This may explain why raloxifene effects on development of Alzheimer’s disease may show the large variability that is seen [ 41 , 98 , 101 ]. In addition, to emphasize apparent anti-viral, as well as anti-bacterial properties of raloxifene, it has been found that it can also be used in treatment against malaria [ 111 ].…”
Section: Brain Diseases Brain Injuries and Underlying Functions mentioning
confidence: 99%